Association between rectal colonisation by Klebsiella pneumoniae carbapenemase-producing K. pneumoniae and mortality: a prospective, observational study. (June 2022) - Cano, Ángela; Gutiérrez-Gutiérrez, Belén; Machuca, Isabel; Torre-Giménez, Julián; Frutos-Adame, Azahara; García-Gutiérrez, Manuel; Gallo-Marín, Marina; Gracia-Ahufinger, Irene; Artacho, María J.; Natera, Alejandra M.; Pérez-Nadales, Elena; Castón, Juan José; et al.
Highlights: Regarding the association of KPC-producing Klebsiella pneumoniae (KPC-Kp) rectal colonisation with crude mortality: Colonisation does not increase crude mortality per se. Colonisation was a necessary although insufficient cause of KPC-Kp infection. Risk of mortality in colonised patients depends on development of severe KPC-Kp infection. ABSTRACT: Objectives: We evaluated the association of Klebsiella pneumoniae carbapenemase-producing K. pneumoniae (KPC-Kp) rectal colonisation with crude mortality and whether this association is independent of the risk of KPC-Kp infection. Methods: This was a prospective cohort study of patients followed-up 90 days after a study of rectal colonisation. Cox regression was used to study the variables associated with crude mortality. Sensitivity analyses for 90-day crude mortality in different subcohorts were performed. Results: A total of 1244 patients (1078 non-colonised and 166 colonised) were included. None of the non-colonised patients and 78 (47.0%) of the colonised patients developed KPC-Kp infection. The 90-day crude mortality was 18.0% (194/1078) in non-colonised patients and 41.6% (69/166) in colonised patients. Rectal colonisation was not associated with crude mortality [hazard ratio (HR) = 1.03, 95% confidence interval (CI) 0.69–1.54; P  = 0.85] when the model was adjusted for severe KPC-Kp infection [INCREMENT-CPE score (ICS) > 7]. KPC-Kp infection with ICS > 7 was associated with an increased risk of all-cause mortality (HR = 2.21, 95% CI 1.35–3.63; P  = 0.002). In the sensitivity analyses, KPC-Kp colonisation was not associated with mortality in any of the analysed subcohorts, including patients who did not develop KPC-Kp infection (HR = 0.93, 95% CI 0.60–1.43; P  = 0.74). Conclusion: KPC-Kp rectal colonisation was not associated with crude mortality. Mortality increased when colonised patients developed severe KPC-Kp infection (ICS > 7). Rectal colonisation was a necessary although insufficient condition to die from a KPC-Kp infection.